Fiction and Physicality: a designerly approach towards complexities of emerging technologies. (28th July 2017) - Hur, Yeup; Sturdee, Miriam; Alonso, Migeul Bruns; Markopoulos, Panos; Alexander, Jason
Abstract: Rapid technological progression results in exciting new ways of interacting with our world whilst simultaneously limiting our experiences. Due to the pervasiveness of emerging technologies, designers are constantly faced with complexities and challenges, which necessitate the use of various tools and methodologies. This paper combines inspiration from the fields of aesthetics of interaction (Overbeek 1999), somaesthetics (Shusterman, 1999), design ethnography (Salvador, 1999), design fiction (Bleecker, 2009) and speculative design (Auger, 2013), to explore a designerly way of overcoming the complexity of implementing technologies into our daily life. We propose a holistic design approach to envision possibilities for emerging technology, integrating the physicality of human bodies with technological materiality. Further, we present a plausible narrative, containing visionary aspects and the investigated methodologies, alongside a series of design concepts that drive the storyline and form the basis for examining social implications, design and future contexts, and improving the way in which designers handle the limitations of a technology driven design approach.